AKTIVITAS EKSTRAK KASAR ENZIM AMILASE DARI BAKTERI Aeromonas hydrophila ISOLAT M1S2 ASAL LAHAN RAWA MANDIANGIN, KALIMANTAN SELATAN - Aynul Hasanah; Ika Oksi Susilawati; Badruzsaufari Badruzsaufari (Bioscientiae, 2024)
Aeromonas hydrophilla isolate M1S2 was isolated from Mandiangin swampy soil, South Kalimantan, and showed potential amylolytic activity by producing an amylase enzyme. This study aims to qualitatively and quantitatively analyze the ability of isolate M1S2 to hydrolyze starch substrate, measure amylase enzyme activity and specific activity of amylase enzyme crude extract, and analyze the effect of temperature and pH on amylase enzyme activity. The results of this study showed that isolate M1S2 was able to hydrolyze starch substrate with an amylolytic index of 1.23. In addition, the Fehling test indicated that the isolate produced amylase enzyme in the culture medium. The amylase enzyme activity and specific activity of isolate M1S2 were 0,00072 U/mL and 0.1634 U/mg, respectively. The amylase enzyme reached optimum activity at 40 0C and pH 6.